Regional Movements of Reef Manta Rays (Mobula alfredi) in Seychelles Waters - Peel, Lauren R.; Stevens, Guy M. W.; Daly, Ryan; Keating Daly, Clare A.; Collin, Shaun P.; Nogués, Josep; Meekan, Mark G. (Frontiers in Marine Science, 2020)
The decline in numbers of reef manta rays (Mobula alfredi) throughout their range has highlighted the need for improved information on their spatial ecology in order to design effective conservation strategies for vulnerable populations. To understand their patterns of movement in Seychelles we used three techniques – archival pop-up satellite tags, acoustic tags, and photo-identification – and focussed on the aggregation at D’Arros Island and St. Joseph Atoll within the Amirantes Group. Mobula alfredi were photographed within six of the seven Island Groups of Seychelles, with 64% of individuals being resighted at least once between July 2006 and December 2019 over timeframes of 1 to 3,462 days (9.5 years; median = 1,018 days). Only three individuals from D’Arros Island were resighted at a second aggregation site located more than 200 km away at St. François Atoll during photo-identification surveys. Satellite-tracked M. alfredi (n = 5 tracks; maximum 180 days) remained within the boundary of the Seychelles Exclusive Economic Zone, where they spent the majority of their time (87%) in the upper 50 m of the water column in close proximity to the Amirantes Bank. The inclusion of acoustic tagging data in the models of estimated satellite-track paths significantly reduced the errors associated with the geolocation positions derived from archived light level data. The insights gained into the patterns of horizontal and vertical movements of M. alfredi using this multi-technique approach highlight the significance of D’Arros Island and St. Joseph Atoll, and the wider Amirantes Group, to M. alfredi in Seychelles, and will benefit future conservation efforts for this species within Seychelles and the broader Western Indian Ocean.